Evolution of Mammals - Matos, Raymonde, author 648775 (Delhi, India : Research World, 2012)
The evolution of mammals within the synapsid lineage ( mammal-like-reptiles) was a gradual process that took approximately 70 million years, beginning in the mid-Permian. By the mid-Triassic, there were many species that looked like mammals, and the first true mammals appeared in the early Jurassic. The earliest known marsupial, Sinodelphys, appeared 125 million years ago in the early Cretaceous, around the same time as Eomaia, the first known eutherian (member of placentals ""parent" group); and the earliest known monotreme, Teinolophos, appeared two million years later. After the Cretaceous - Tertiary extinction wiped out the non-avian dinosaurs (birds are generally regarded as the surviving dinosaurs) and several other mammalian groups, placental and marsupial mammals diversified into many new forms and ecological niches throughout the Tertiary, by the end of which all modern orders have appeared. From the point of view of phylogenetic nomenclature, mammals are the only surviving synapsids. The synapsid lineage became distinct from the sauropsid ("reptile") lineage in the late Carboniferous period, between 320 and 315 million years ago, and were the most common and largest land vertebrates of the Permian period. But in the Triassic period a previously obscure group of sauropsids, the archosaurs, became the dominant vertebrates and one archosaur group, the dinosaurs, dominated the rest of the Mesozoic era. These changes forced the Mesozoic mammaliforms ("nearly mammals") into nocturnal niches, and may have contributed greatly to the development of mammalian traits such as endothermy, hair and a large brain. Later in the Mesozoic mammals spread into other ecological niches, for example aquatic, gliding and even preying on dinosaurs.